MMSpace: Kinetically-augmented telepresence for small group-to-group conversations - Otsuka, Kazuhiro (Proceedings of the Workshop on Future Trends of Distributed Computing Systems, 2016)
A novel research prototype, called MMSpace, was developed for realistic social telepresence in small group-to-group conversations. MMSpace consists of kinetic display avatars, which can change pose and position by automatically mirroring the remote user's head motions. To fully explore its potential beyond previous alternatives, MMSpace has the following novel features. First, it targets symmetric group-to-group telepresence. Second, the kinetic avatars of MMSpace can produce highly accurate, low latency, and silent physical motions, by using 4-Degree-of-Freedom (DoF) direct-drive actuators, and they can express a wide range of natural human behaviors like head gestures and changing attitudes, as well as indicating the focus of attention. Third, MMSpace supports eye contact between every pair of participants, by integrating i) directional visual attention cues indicated by avatar's kinetic pose change, ii) line-of-sight alignment among the positions of persons, avatars and cameras, and iii) attention-based camera switching, which allows an avatar to always show its owner's face looking directly toward the person that the avatar's owner is looking at. The prototype targets the 2 × 2 setting, and subjective evaluations based on group discussions indicate that the kinetic display avatar is superior to static displays in various aspects including gaze-awareness, eye-contact, perception of other nonverbal behaviors, mutual understanding, and sense of telepresence.